Enkapsulasi Urea Menggunakan Biokomposit Zeolit Alam-Alginat-Pati Sagu sebagai Model Pupuk Lepas Lambat (Slow Release Fertilizer) - Suci, Ida Ayu; Astar, Ismail (Al-Kimia, 2022)
The urea fertilizer was encapsulation with the compositions of natural zeolite-alginate-sago starch biocomposite for developing of slowed-release properties. The characteristics of biocomposites such as FTIR, SEM, and nitrogen release tests were evaluated. Fourier transform infrared spectroscopy showed the presence of natural zeolite-alginate-sago starch biocomposite. The SEM images showed the surface morphology of urea has been coated by natural zeolite-alginate-sago starch biocomposite. Nitrogen release tests on natural zeolite-alginate-sago starch biocomposites with concentrations of 20% was the composition with the best results in holding urea encapsulated. This study indicates that natural zeolite-alginate-sago starch biocomposites are a alternative candidate for the development of the efficient slowed-release formulation of urea.